Persinggungan Hukum dengan Masyarakat dalam Kajian Sosiologi Hukum - Mushafi Mushafi; Ismail Marzuki (Jurnal Cakrawala Hukum, 2018)
The intersection of law and society in sociological discourse. In this article a lot is explained about dialogical correlation between law and society in social life. Conceptually law and society have mutually complementary relationships related to their existence. In the legal sociology paradigm, society is a resource that gives life (to nature) and moves the law. Whereas the community lives the law with values, ideas and concepts, besides that the community also supports the law by fertilizing the legal awareness (legal culture) of the community to carry out the law. Social changes and legal changes or vice versa do not always take place together. This means that in certain circumstances legal developments may lag behind the development of other elements in society or maybe vice versa. Law is one means of social change that exists in society. Karaena, there is a relationship of interaction between the legal sector and social changes that occur in the community. Conflicts that occur can cause losses, because they are usually accompanied by violations of the rights and obligations of one party to another party.How to cite item: Mushafi, M., Marzuki, I. (2018). Persinggungan Hukum dengan Masyarakat dalam Kajian Sosiologi Hukum. Jurnal Cakrawala Hukum, 9(1), 50-58. doi:https://doi.org/10.26905/idjch.v9i1.2168